1996
DOI: 10.1177/073490419601400207
|View full text |Cite
|
Sign up to set email alerts
|

The Smoldering Potential of Used Upholstery Fabrics: Unsoiled vs. Soiled

Abstract: The objective of this research was to determine the effect of soil ing, through wear, on the smoldering potential of upholstery fabrics. This research was done to test the supposition that smolder resistant fabrics on new furniture will become more susceptible to smoldering with soiling and age. This is shown not to be the case. Sixty used upholstery fabrics were collected from eight upholstery shops, and areas of each fabric were determined to be either "soiled" or "unsoiled." A soiled area is an exposed surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thirty-three of the fabrics, 66%, were lesss than 12 oz/yd2. A recent study of used upholstered furniture fabrics suggests that areal density distributions similar to that of the fifty fabrics also may be found on older furniture [11]. CONCLUSIONS Differences in the propensity of cigarettes to ignite upholstered furniture mock-ups, reported on the basis of tests using cotton duck fabrics, were not reproduced using the commercial upholstery fabrics.…”
Section: Analysis and Discussionmentioning
confidence: 92%
“…Thirty-three of the fabrics, 66%, were lesss than 12 oz/yd2. A recent study of used upholstered furniture fabrics suggests that areal density distributions similar to that of the fifty fabrics also may be found on older furniture [11]. CONCLUSIONS Differences in the propensity of cigarettes to ignite upholstered furniture mock-ups, reported on the basis of tests using cotton duck fabrics, were not reproduced using the commercial upholstery fabrics.…”
Section: Analysis and Discussionmentioning
confidence: 92%
“…Putted cigarette (Figure 3cII) started initiation quicker than Sample 1 (Figure 3aI,II) and Sample 2 (Figure 3bI,II). Wanna [38] points out the flammability of cotton and emphasizes the need for its retarding treatment, e.g., using appropriate salts. The given quantity of cotton influenced the behavior of the material in the experiment (Figure 3c).…”
Section: The Ignition Using An Equivalent To a Matchmentioning
confidence: 99%
“…Laundering, or even water soaking, of cotton fabrics often reduces the metal ion content to such a level that the fabrics are not ignited by cigarettes. Soiling of cotton or rayon fabrics can affect smouldering potential [27,28].…”
Section: Combustionmentioning
confidence: 99%
“…Whether the upholstery fabric is soiled or used also can affect smouldering potential and is most likely dependent on the type of soiling. Wanna and co-workers reported that used or soiled fabrics became more resistant to smouldering ignition compared with the unsoiled fabrics [27,28].…”
Section: Cigarette Smouldering Ignitionmentioning
confidence: 99%